1997
DOI: 10.1111/1523-1747.ep12285633
|View full text |Cite
|
Sign up to set email alerts
|

C3 Production of Cultured Human Epidermal Keratinocytes in Enhanced by IFNγ and TNFα through Different Pathways

Abstract: We investigated the regulation of C3 production by human cultured epidermal keratinocytes by enzyme-linked immunosorbent assay. The results showed that IFNgamma and TNFalpha enhanced the synthesis of C3 by epidermal keratinocytes in a concentration-dependent manner. Moreover, a protein kinase C (PKC) inhibitor blocked C3 production, whereas PMA enhanced it. There was a synergistic effect between IFNgamma and TNFalpha. In experiments to investigate the role of protein tyrosine kinase (PTK) in C3 production, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…To facilitate the alternative complement pathway, its two essential components, factor B and C3, are produced in the skin by cultured human keratinocytes (77). Furthermore, we recently demonstrated that C3 is more effectively produced by differentiated keratinocytes, such as those found in the upper epidermis, than by actively proliferating keratinocytes comprising the basal cell layer, and that T-cell-derived cytokines such as IFN-g and TNF-a synergistically enhance the generation of C3 from these cells (78). Thus, proinflammatory mediators, IL-8 and C3 may be produced at both the ''acute'' and ''chronic'' inflammatory sites (68, 5 79) as long as there are activated T cells and macrophages.…”
Section: Evidence Of Complement Activation In Psoriasismentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the alternative complement pathway, its two essential components, factor B and C3, are produced in the skin by cultured human keratinocytes (77). Furthermore, we recently demonstrated that C3 is more effectively produced by differentiated keratinocytes, such as those found in the upper epidermis, than by actively proliferating keratinocytes comprising the basal cell layer, and that T-cell-derived cytokines such as IFN-g and TNF-a synergistically enhance the generation of C3 from these cells (78). Thus, proinflammatory mediators, IL-8 and C3 may be produced at both the ''acute'' and ''chronic'' inflammatory sites (68, 5 79) as long as there are activated T cells and macrophages.…”
Section: Evidence Of Complement Activation In Psoriasismentioning
confidence: 99%
“…Although C3, the key component of the complement system, tends to be produced more in the upper, more differentiated keratinocytes (78), the exact mechanisms that lead to complement activation in skin lesions remain to be elucidated, particularly on the surface of corneocytes. Exocytosis of inflammatory cells into the lesional epidermis, which is prominent in the edematous suprapapillary portion of the lesional epidermis, possibly results in damage of the basement membrane zone and the overlying epidermal cells (80).…”
Section: Evidence Of Complement Activation In Psoriasismentioning
confidence: 99%
“…4), it is most likely that C3 is activated and coupled to viral Ags within the local lymph node that drains the site of infection. Although the regulation of C3 synthesis by macrophages in vivo is not known, studies with human and murine cell lines indicate that C3 secretion can be induced by multiple cytokines such as IFN-␥ (46, 47), IL-6 (48), TNF (38), IL-1 (49), and IL-2 (40). Macrophages secrete other components of complement in addition to C3 and in particular C4, C2, C1r, C1s, and C1q (36,50,51).…”
Section: Figure 2 Infectious Hsv-1 Induces Significantly Greater Ab mentioning
confidence: 99%
“…However, a number of extrahepatic sources of C3 synthesis have been described. These include myeloid lineage cells such as monocytic cells (36) and polymorphonuclear leukocytes (37) as well as non-bone marrow (non-BM)-derived sources such as epidermal keratinocytes (38), kidney tubular epithelial cells (39,40), and umbilical vein endothelial cells (41). The potential of macrophage-derived C3 in the humoral response to protein Ag was determined using C3 Ϫ/Ϫ BM chimeras that received wild-type (WT) BM (WT BM3 C3 Ϫ/Ϫ ).…”
mentioning
confidence: 99%
“…Nonhepatic cells, such as keratinocytes (17), kidney tubular epithelial cells (18), and macrophages (19), provide additional sources of C3. The contribution to the circulation from these secondary sources varies greatly depending on the system, from clearly detectable (20,21) to negligible (22,23).…”
mentioning
confidence: 99%